The Impact of Prompts and Feedback on the Performance during Multi-Session Self-Regulated Learning in the Hypermedia Environment - Wang, Yurou; Zhang, Haobo; Wang, Jue; Ma, Xiaofeng (Journal of intelligence, 2023)
The hypermedia environment is among the most prevalent contemporary self-regulated learning (SRL) environments; however, methods for improving the effectiveness of students’ multi-session SRL in such environments remain under discussion. In this study, two experiments were conducted to explore whether and how prompts and feedback benefit performance during multi-session SRL in a hypermedia learning environment. A total of 76 senior students participated in Experiment 1, which used a mixed 2 (prompting condition: prompt, no prompt) × 2 (feedback condition: feedback, no feedback) × 2 (learning session: Session 1 and Session 2) design to explore the effects of prompting and feedback on the multi-session learning process in a hypermedia environment. The results indicated that, in learning Session 1, performance in the prompt condition was significantly better than in the unprompted condition, with or without feedback; in learning Session 2, participants in the prompt condition with feedback performed significantly better than those in the other three conditions. Students in the group with a prompt and feedback had the most accurate meta-comprehension absolute accuracy in both learning sessions. Experiment 2 recruited 94 secondary school students to further explore whether the combination of prompts and different types of feedback led to different learning outcomes according to the division of feedback timing. A mixed 2 (prompt condition: prompt, no prompt) × 3 (feedback condition: delayed feedback, immediate feedback, no feedback) × 2 (learning session: Session 1 and Session 2) design was used. The results indicated that, in learning Session 1, the prompt condition outperformed the unprompted condition with or without feedback; in learning Session 2, students with prompted delayed feedback outperformed the other five conditions. We also found that although there was no significant difference in meta-comprehension monitoring accuracy between delayed and immediate feedback, both groups performed significantly better than those in the no feedback condition. These results suggest that the combination of prompts and feedback in hypermedia environments facilitates student performance better than prompts or feedback alone; this improvement may be related to the correction of poor internal student feedback.